Madden, David y Marcuse, Peter (2018). En defensa de la vivienda. Madrid: Capitán Swing Libros, 230 p. - Salinas Arreortua, Luis Alberto (El Colegio de México A.C., 2021)
The housing issue has sparked a wide variety of discussions about its most pressing problems (such as deficit, access, construction materials, location, overcrowding, among others) and actions to address these problems. The critical analysis proposed by these authors breaks with conformism and the positive evaluations that have been built from political and academic discourses on interventions in housing matters.